(untitled) (International Conference on Computers in Education, 2016)
Instructors who wish to disseminate digital content to learners in an economical manner must consider the costs of (1) content creation (software and hardware), (2) content dissemination (data transfer costs), and (3) content access (hardware and software needed to view content). In this paper, we present a novel technique – photocasting – to greatly reduce these three costs in a one-to-one learning environment. Our technique has minimal requirements: a low-end smartphone for instructors and learners, and a modest additional effort by instructors after recording their digital notes. The delivery cost is primarily determined by the size of the audio, and is approximately 100 times smaller than the size of a traditional video of comparable quality. We have implemented our technique as a prototype for the Android platform, and we report initial results of a small-scale user study with three participants: a school teacher, a private tutor, and a high-school student.